Oral eradication therapy for melioidosis: Important but not without risks. (March 2019) - Sullivan, R.P.; Ward, L.; Currie, B.J.
Highlights: Adverse effects from oral trimethoprim-sulfamethoxazole therapy are common in northern Australia. Prolonged intravenous phase therapy remains important in northern Australia. A subset of patients may benefit from reduction in duration or even omission of the eradication therapy phase. Abstract: Objectives: The purpose of this study was to quantify the adverse effects from oral eradication therapy for melioidosis, which is usually with high dose trimethoprim-sulfamethoxazole for 3–6 months. Methods: This retrospective cohort study reviewed side effects from oral eradication therapy in patients presenting with first episode culture-confirmed melioidosis in the tropical north of Australia's Northern Territory between 1st October 2012 and 1st January 2017. Results: 234 patients presented for the first time with culture-confirmed melioidosis. Of these, 16 (6.8%) died during the intensive phase treatment and 6 (2.6%) did not have complete treatment at Royal Darwin Hospital. Of the remaining 212 patients, 203 (95.8%) were initially prescribed trimethoprim-sulfamethoxazole as oral eradication therapy, 6 (2.8%) were prescribed doxycycline and 3 (1.4%) had no eradication therapy. Of the 203 prescribed trimethoprim-sulfamethoxazole, 61 (30.0%) experienced adverse effects, which necessitated a cessation, a change in antibiotic or reduction in dose. Conclusions: In patients treated for melioidosis in northern Australia there are high rates of adverse effects from oral trimethoprim-sulfamethoxazole, frequently necessitating a change in therapy or a reduction in dose. Given the side effects and low rates of oral therapy completion in our region we emphasise the importance of the prior often prolonged intensive phase intravenous therapy and using weight based trimethoprim-sulfamethoxazole dosing for eradication therapy.